Study on the interaction between carbonyl-fused N-confused porphyrin and bovine serum albumin by spectroscopic techniques - Yu, Xianyong; Liao, Zhixi; Jiang, Bingfei; Zheng, Lingyi; Li, Xiaofang (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2014)
[Display omitted] •The interaction between BSA and CF-NCP was studied.•The fluorescence quenching mechanism is a static quenching procedure.•The binding constants and binding sites were calculated.•Electrostatic force played a major role in stabilizing the complex.•The conformation of BSA was affected by CF-NCP. The interaction between carbonyl-fused N-confused porphyrin (CF-NCP) and bovine serum albumin (BSA) was investigated by fluorescence and ultraviolet–visible (UV–Vis) spectroscopy. The results indicated that CF-NCP has strong ability to quench the intrinsic fluorescence of BSA by forming complexes. The binding constants (Ka), binding sites (n) were obtained. The corresponding thermodynamic parameters (ΔH, ΔS and ΔG) of the interaction system were calculated at three different temperatures. The results revealed that the binding process is spontaneous, and the acting force between CF-NCP and BSA were mainly electrostatic forces. According to Förster non-radiation energy transfer theory, the binding distance between CF-NCP and BSA was calculated to be 4.37nm. What is more, the conformation of BSA was observed from synchronous fluorescence spectroscopy.